Neurosurgery - Lumenta, Christianto B.; Di Rocco, Concezio; Haase, Jens; Mooij, J.J.A (European Manual of Medicine, 2010)
In a specialized field such as neurosurgery, highly specific knowledge is required. Training programs in the EU vary, making it difficult to standardize medical training. This manual forms the basis for a European consensus in neurosurgery. It is written for residents, students and physicians with a special interest in neurosurgery. Diagnostic and therapeutic procedures are detailed according to localization (cranial, spinal, peripheral nerves) with special consideration given to congenital defects and pediatric neurosurgical disorders, functional and stereotactic neurosurgery, as well as critical neurosurgical care. Each chapter contains the basics of anatomy and physiology. The book is well-organized and clearly structured according to each entity and its neurosurgical treatment options. A better understanding of specific neurosurgical problems will help practicing neurosurgeons provide better medical care for their patients, and will also provide the neurosurgery resident with a reliable European standard for step-by-step management of neurosurgical problems, which will prove useful when preparing for the board examination.